Retrospective investigation of non-traumatic small intestine perforations: Our single center 7-year clinical experiences - Sebnem Cimen; Burak Ucaner; Ahmet Kamburoglu; Cilga Ecem Lamba (Medicine Science)
Non-traumatic small intestine perforations (NTSIP) constitute a rare cause of acute surgical pathologies and have a high mortality and morbidity if not treated in time. Since the clinical presentation of the disease is non-specific, there may be delays in its diagnosis. Despite medical improvements, the mortality of NTSIP is still high today. This study aimed to investigate non-traumatic small intestine perforation, an entity that continues to pose diagnostic and therapeutic challenges for clinicians, through a retrospective analysis of patients who underwent surgery for this condition. Patients, who were operated due to NTSIP in our general surgery clinic between June 2017 and June 2024, were retrospectively examined. Patients under the age of 18 were not included in the study. In addition, cases with colon and/or stomach perforation were excluded from the study. Fifty-nine patients with NTSIP were included in the study. The mean age of the patients was determined as 61.9 ± 18.4 (19–86 years). Male/female ratio was 1.1. The most common causes of perforation were found as non-specific causes (35.6%), tumor (27.1%) and herniation (16.9%), respectively. Mortality rates were 20% in perforations due to herniation, 50% mesenteric ischemia and 62.5% tumors. NTSIP is a condition whose preoperative final diagnosis is difficult, whose surgical treatment selection is still discussed and which is an acute abdomen cause with high mortality and morbidity in case of delayed diagnosis and treatment. It is an important cause of acute abdomen, which should be evaluated with the selection of patient-specific surgical technique and multidisciplinary approach when necessary. As more homogeneous and larger-population studies on the subject are added to the literature, the questions in the minds of clinicians will be answered. [Med-Science 2024; 13(4.000): 783-7]